Rotating savings and credit association, its members' diversity, and higher‐level functional capacity: A 3‐year prospective study from the Japan Gerontological Evaluation Study. Issue 12 (22nd November 2019) - Sato, Koryu; Kondo, Naoki; Kondo, Katsunori
Abstract : Aim: A rotating savings and credit association – an informal local microfinance group – provides community‐dwelling older adults with cohesive social capital. This study examined whether participation in mujin, a traditional Japanese rotating savings and credit association, affected the maintenance of higher‐level functional capacity in older adults. Methods: We studied 10 991 older adults living in 24 municipalities in Japan who were aged ≥65 years, and physically and cognitively independent. We carried out a baseline survey in 2013 and a follow‐up survey in 2016. Higher‐level functional capacity, consisting of instrumental activities of daily living, intellectual activity and social role, was assessed using the Tokyo Metropolitan Institute of Gerontology Index of Competence. To address potential reverse causation, we used stabilized inverse probability weights to balance characteristics at baseline between mujin participants and non‐participants. Results: In our analytic sample, 406 out of 10 991 older adults (3.7%) participated in mujin at the baseline. Our weighted logistic regression showed that mujin participants were more likely to maintain higher‐level functional capacity (i.e. full marks in the Tokyo Metropolitan Institute of Gerontology Index of Competence) 3 years later compared with non‐participants (odds ratio 1.75, 95% confidence interval 1.29–2.39). Furthermore, independent social role functioning and intellectual activity were associated with participation in mujin for an equal number of both sexes, as well as people of high social standing. Conclusions: The present study suggests that rotating savings and credit associations can help older adults maintain their independence in a higher‐level functional capacity. Furthermore, the members' diversity might add to these beneficial effects. Geriatr Gerontol Int 2019; 19: 1268–1274 .